Assessment of Structural and Functional Abnormalities of the Myocardium and the Ascending Aorta in Fetus with Hypoplastic Left Heart Syndrome. (15th February 2016) - Jiang, Yan; Xu, Yali; Tang, Jinliang; Xia, Hongmei
Abstract : Aims . To detect anatomical and intrinsic histopathological features of the ascending aorta and left ventricular (LV) myocardium and evaluate right ventricular (RV) function in fetuses with hypoplastic left heart syndrome (HLHS). Methods . Twenty-five fetuses diagnosed with HLHS were followed up in the antenatal and postpartum periods. 12 necropsy heart specimens were analyzed for morphological and histological changes. Results . Prenatal echocardiography and pathologic anatomy displayed the typical characteristics of HLHS as a severe underdevelopment of the LV in the form of mitral stenosis or atresia or as aortic atresia or stenosis, with a decreased ratio of aortic diameter to pulmonary artery diameter (median of 0.49 with a range of 0.24 to 0.69, p ≤ 0.001 ) and a higher ratio of RV diameter to LV diameter (median of 2.44 with a range of 1.33 to 6.25, p ≤ 0.001 ). The RV volume, stroke volume, and cardiac output in HLHS fetuses were increased compared with the gestational age-matched normal controls (p < 0.01 ). Histological changes in the 12 HLHS specimens included LV myocardial fibrosis, aortic elastic fragmentation, and fibrosis. Conclusions . In addition to severe anatomical deformity, distinct histological abnormalities in the LV myocardium and aortic wall were identified in the fetuses with HLHS. RV function damage may be potentially exists.